Advances in IPTV system architecture and streaming media technology - Xiang-hai WANG; Zhi-huan CONG; Ling-ling FANG (Tongxin xuebao)
IPTV architecture development was reviewed and compared.Especially,the detail analysis about multimedia session building procedures that related to IMS-based IPTV was given.Then on the basis of above,some streaming media technologies which were important to IPTV system application was proposed.Finally,the direction of future research of IPTV related technologies was prospected.